2016
DOI: 10.1109/tpwrs.2015.2393636
|View full text |Cite
|
Sign up to set email alerts
|

Areal Solar Irradiance Estimated by Sparsely Distributed Observations of Solar Radiation

Abstract: Photovoltaic (PV) power generation is being decentralized and introduced on various scales in electric power systems that are expanding over wider areas. To understand the effect of PV power generation on these electric power systems (in areas ranging from power generation operation and control to voltage management of the distribution system), areal solar irradiance must be estimated for a target area, particularly, for the position and surface area that correspond to the PV power generation equipment locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Therefore the success of two algorithms in detecting cloud motion is estimated from simulated dense ground data: cross-spectral analysis (CSA) and the cross-correlation method (CCM). In CSA, the cloud speed and direction are estimated by cross-spectral analysis of the irradiance data at some given locations (sites) through the domain (Inoue et al, 2012;Shinozaki et al, 2014). The CSA method suggested by Inoue et al (2012) and Shinozaki et al (2014) is restricted by the spatial arrangement of the sites such that the cloud direction may be inaccurate if there are only a few distinct relative angles between the pairs of the chosen sites.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore the success of two algorithms in detecting cloud motion is estimated from simulated dense ground data: cross-spectral analysis (CSA) and the cross-correlation method (CCM). In CSA, the cloud speed and direction are estimated by cross-spectral analysis of the irradiance data at some given locations (sites) through the domain (Inoue et al, 2012;Shinozaki et al, 2014). The CSA method suggested by Inoue et al (2012) and Shinozaki et al (2014) is restricted by the spatial arrangement of the sites such that the cloud direction may be inaccurate if there are only a few distinct relative angles between the pairs of the chosen sites.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…In CSA, the cloud speed and direction are estimated by cross-spectral analysis of the irradiance data at some given locations (sites) through the domain (Inoue et al, 2012;Shinozaki et al, 2014). The CSA method suggested by Inoue et al (2012) and Shinozaki et al (2014) is restricted by the spatial arrangement of the sites such that the cloud direction may be inaccurate if there are only a few distinct relative angles between the pairs of the chosen sites. To remove the restriction, a new CSA approach for cloud motion direction is proposed by selecting the direction with least variation for all the velocities in the cloud motion direction.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have confirmed that multi-task learning approaches can be useful for distributed solar irradiance or solar power forecasting, finding that cross-site information is relevant [33,35]. Several studies build on the early work of [26] and consider co-kriging methods for distributed solar irradiance forecasting or spatial prediction (notably [27,33]). Other approaches include a range of linear statistical methods, shown to be competitive at shorter horizons, and neural network methods [16,30,31].…”
Section: Multi-task Solar Power Forecastingmentioning
confidence: 99%